A Genealogical Study of Kuang Qizhao's An English and Chinese Lexicon (1868). (13th October 2022) - Li, Rui; Zhang, Chun; Xu, Hai
Abstract: Embedded in historical and genealogical research, this study investigates the influence of English-Chinese dictionaries compiled by missionaries on Kuang Qizhao's (1836?–1891?) An English and Chinese Lexicon, compiled in part from those of Morrison, Medhurst and Williams (1868). Drawing on Hartmann's genealogical approach and the lexicographical findings and linguistic evidence presented in three case studies, we argue that Kuang depended not only on Walter Henry Medhurst's (1796–1857) English and Chinese Dictionary (1847–48), Samuel Well Williams' (1812–1884) An English and Chinese Vocabulary (1844) and Robert Morrison's (1782–1834) English and Chinese dictionary (1822), as indicated in the dictionary title, but also on Wilhelm Lobscheid's (1822-1893) An English and Chinese Dictionary (1866–69) for his own dictionary. And yet Kuang never acknowledged Lobscheid's dictionary as one of his source dictionaries. This article discusses the reasons why Kuang failed to acknowledge the importance of Lobscheid's contribution to his dictionary. It is expected to that the findings we have made will provide insights into the genealogical study of English-Chinese dictionaries in general, as well as confirming Kuang's remarkable merit in compiling his English-Chinese dictionary in the 19th century.